STRATEGI PENINGKATAN PRESTASI BELAJAR MELALUI BIMBINGAN ORANG TUA DALAM KELUARGA DAN PRAKTIKUM KEAGAMAAN SEKOLAH (MGMP PAI Jawa Barat, 2022)
Parents are not enough to entrust their children's religious education to the school alone, the teacher is the child's parent at school. Good cooperation between parents and the school is certainly needed in educating children, so that the learning outcomes of children can be realized in their daily lives. All of that, of course, is returned to the supervisor himself, this is the family and teacher. Whatever the activity, the ultimate goal of learning Islamic Religious Education in schools is so that students can practice what they receive about religious learning directly. So success in learning Islam is actually not only on academic ability, but more than that it is about the appreciation of religion and direct practice in living life. To carry out religious practices in schools, it can be done by means of intracurricular activities by presenting innovative and varied learning so that students do not get bored in learning, as well as extracurricular activities in the form of congregational prayers, regular Friday recitations, Islamic boarding schools, alms and Intensive Islamic Studies. While parental guidance at home can be in the form of habituation, advice, attention, and punishment.